2018
DOI: 10.4103/0973-1482.180683
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of immunohistochemical expression of TP53 and CDKN1A in oral epithelial dysplasia and oral squamous cell carcinoma

Abstract: The expression of TP53 in OED highlights its role in initial carcinogenesis. Although the role of CDKN1A in the cell cycle has been documented, its relationship to various clinical and pathological variables of OSCC and its different treatment modalities could not be adequately assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Researchers demonstrated p53’s role in differentiating grades of dysplasia. Pandya et al [ 53 ] showed that the difference in expression was statistically significant between mild and severe dysplasia. The difference in TP53 expression between mild and severe dysplasia was statistically significant, according to Patil et al [ 54 ].…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers demonstrated p53’s role in differentiating grades of dysplasia. Pandya et al [ 53 ] showed that the difference in expression was statistically significant between mild and severe dysplasia. The difference in TP53 expression between mild and severe dysplasia was statistically significant, according to Patil et al [ 54 ].…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 99%
“…Cell division and proliferation p53 [53][54][55]75,76,117], Ki-67 [56,[68][69][70][71][72][73][74][75][76], CD105 [73,74], p63 [39,42,117], CD31 [39], CD34 [43], cycD1 [42], VEGF [43], YAP, Np63 [59], stathmin [80], CDKN1A [53] Epithelial-mesenchymal transition CK5\6 [96], CK19 [98], β-catenin [103,104], N-cadherin [109], E-cadherin [104][105][106][107], TWIST [111], VIM [107,108], PDPN [115,117], MMP-9 [108] Cell death regulation Bcl-2 [123,124], PDCD4 [128], HSP27 [131], cornulin [134] Cellular metabolism HIF-1a [136], iNOS...…”
Section: Relation Of Biomarkers Examples Of Biomarkers For Grading Of...mentioning
confidence: 99%
“…SENP7 also showed a strong relationship with the chemotherapy drugs (Fig 5A–5C). The networks of SENP7 as well as other targets, KAT2B and DTX3L, with chemotherapy drugs showed the strong relationship with TP53 protein, a biomarker of oral cancers [(Figs 5 and 6) [37, 38]. The association of target proteins with TP53 and chemotherapy drugs, especially carboplatin and doxorubicin, should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of p53 expression increase in association with histologic grade of OED [ 105 ]. In fact, p53 expression is present in 80% of oral epithelial hyperplasia [ 106 ] and increases significantly from OL to OSCC in patient samples [ 81 ].…”
Section: Nuclear Biomarkersmentioning
confidence: 99%